Coronary microvascular dysfunction in male patients with Anderson-Fabry disease and the effect of treatment with α galactosidase A. Issue 3 (5th August 2005) - Elliott, P M; Kindler, H; Shah, J S; Sachdev, B; Rimoldi, O E; Thaman, R; Tome, M T; McKenna, W J; Lee, P; Camici, P G
Abstract : Objective: To measure coronary flow reserve (CFR), an index of microvascular function, in Anderson-Fabry disease (AFD) at baseline and after enzyme replacement therapy (ERT). Methods and results: Mean (SD) myocardial blood flow (MBF) at rest and during hyperaemia (adenosine 140 μg/kg/min) was measured in 10 male, non-smoking patients (53.8 (10.9) years, cholesterol 5.5 (1.3) mmol/l) and in 24 age matched male, non-smoking controls (52.0 (7.6) years, cholesterol 4.5 (0.6) mmol/l) by positron emission tomography (PET). Resting and hyperaemic MBF and CFR (hyperaemic/resting MBF) were reduced in patients compared with controls (0.99 (0.17) v 1.17 (0.25) ml/g/min, p < 0.05; 1.37 (0.32) v 3.44 (0.78) ml/g/min, p < 0.0001; and 1.41 (0.39) v 3.03 (0.85), p < 0.0001, respectively). This coronary microvascular dysfunction was independent of cholesterol concentrations. PET was repeated in five patients after 10.1 (2.3) months of ERT; resting and hyperaemic MBF and CFR were unchanged after ERT (0.99 (0.16) v 0.99 (0.16) ml/g/min; 1.56 (0.29) v 1.71 (0.3) ml/g/min; and 1.6 (0.37) v 1.74 (0.28), respectively; all not significant). Conclusions: The results of the present study show that patients with AFD have very abnormal coronary microvascular function. These preliminary data suggest that ERT has no effect on coronary microvascular dysfunction. Further work is necessary to determine whether treatment at an earlier stage in the course of the disease may improve coronary microvascular function in patients with AFD.